2007
DOI: 10.1111/j.1556-4029.2007.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Body Packer: Acute Poisoning Death Due to Massive Leaking of Methamphetamine

Abstract: We encountered three methamphetamine (MA) body packers presenting simultaneously, one of whom died. Three Nigerian men (39, 35, and 37 years old) who attempted to smuggle were found to contain 35 (498 g), 21 (292 g), and 5 packages (73 g) of methamphetamine hydrochloride (MA-HCl) in their stomachs, respectively. Packages were wrapped with plastic film and Scotch tape. The 39-year-old man died with acute poisoning from c. 20 g of MA-HCl that had leaked from the packages into the stomach. His plasma MA concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 15 publications
(20 reference statements)
1
13
0
1
Order By: Relevance
“…To determine Meth effects on RMP of HFAs, we assessed RMP that was exposed to 20 or 100 μM Meth in vitro . We found that both 20 μM Meth ( n = 17, −35.6 ± 1.8 mV) that mimicked non-lethal blood levels of Meth in Meth users (Melega et al 2007), and 100 μM Meth ( n = 12, −37.4 ± 2.9 mV) that was similar lethal Meth levels (Takekawa et al . 2007; Kiely et al 2009), induced a significant RMP depolarization in HFAs compared to those in the control condition ( n = 37, −43.8 ± 1.4 mV; One-way ANOVA : F (2,63) = 6.119, p = 0.004) (Fig.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…To determine Meth effects on RMP of HFAs, we assessed RMP that was exposed to 20 or 100 μM Meth in vitro . We found that both 20 μM Meth ( n = 17, −35.6 ± 1.8 mV) that mimicked non-lethal blood levels of Meth in Meth users (Melega et al 2007), and 100 μM Meth ( n = 12, −37.4 ± 2.9 mV) that was similar lethal Meth levels (Takekawa et al . 2007; Kiely et al 2009), induced a significant RMP depolarization in HFAs compared to those in the control condition ( n = 37, −43.8 ± 1.4 mV; One-way ANOVA : F (2,63) = 6.119, p = 0.004) (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…To advance our understanding for the Meth impact on K + channel activity and its underlying mechanism(s) in HFAs, we performed electrophysiological studies using whole-cell voltage-clamp recording of HFAs following acute Meth exposure (20 and 100 μM) in vitro . We selected such concentrations based on that the blood levels of Meth in ‘recreational’ users are reported at 0.2–17 lM (Melega et al 2007); while higher Meth blood levels (~ 58–400 μM) could be toxic/fatal (Takekawa et al 2007; Kiely et al 2009). These clinical studies provide us the opportunity to suggest and use such ‘recreational’ and ‘fatal/toxic’ doses of Meth in the present study.…”
mentioning
confidence: 99%
“…As such, we chose intravenous administration of METH in our study because this is a common route [18] that is employed by abusers to rapidly raise the blood concentration of METH to euphoric levels. At the same time, we chose to employ high doses of METH that would result in cardiovascular collapse and fatality to mimic observations from clinical conditions [19], [20]. Compared to its primary metabolite amphetamine, METH is more lipid-soluble, with enhanced transport across the blood-brain barrier and stability against enzymatic degradation by monoamine oxidase [21].…”
Section: Discussionmentioning
confidence: 99%
“…Methamphetamine (MTA), as a novel excitatory drug, has been used frequently and illegally worldwide 1 . It can cause varying degrees of damage to the vital organs and mental system of human [2][3][4] , with plenty of forensic case reports of MTA poisoning occurring [5][6][7][8] . Therefore, the efficient determination of MTA is practically essential for forensic toxicological identification.…”
Section: Introductionmentioning
confidence: 99%